Developments in quantitative dimensional synthesis (1970–present): four-bar path and function generation. Issue 9 (2nd September 2018) - Lee, Wen-Tzong; Russell, Kevin
Abstract: Dimensional synthesis is a type of inverse problem in linkage kinematics where the objective is to calculate the linkage dimensions required to achieve prescribed linkage output motion. It includes three distinct subcategories: motion generation, path generation and function generation. The authors' first work surveyed developments in quantitative four-bar motion generation. This work concludes the presentation of developments in four-bar dimensional synthesis by surveying the developments made in quantitative four-bar path and function generation since 1970. While early path and function generation methods (like motion generation methods) were primarily qualitative, ongoing advancements in computing hardware and software continue to make quantitative motion generation more practical.